Pendekatan Konseptual dalam Memahami Analisis Real untuk Pemula - Endha Istiqomah; Ristia Rahmadani; Annisah Kurniati; Suci Yuniati; Depriwana Rahmi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Real Analysis is a fundamental course in mathematics education characterized by its deductive and axiomatic structure, which requires logical, systematic, and conceptual understanding. However, many studies have shown that students often face difficulties in grasping abstract concepts and constructing mathematical proofs deductively. Lestari (2015) found that most students were only able to conduct proofs inductively, while their deductive proof skills remained low due to weak prerequisite knowledge and lack of formal reasoning practice. Meanwhile, Darmadi, Sanusi, and Rifai (2024) explained that students’ difficulties in understanding formal definitions and the structure of real numbers indicate the need for a learning approach that emphasizes conceptual comprehension. This article employs a literature review approach to analyze the application of conceptual approaches in helping beginners understand Real Analysis. The results show that a conceptual approach enhances students’ understanding of the meaning behind mathematical symbols and procedures, helps them build connections among concepts such as limits, continuity, and the real number system, and gradually develops their deductive reasoning skills. Therefore, applying a conceptual approach in Real Analysis learning is an essential strategy to help students achieve deep, logical, and meaningful understanding.